KEPEMIMPINAN MANAJEMEN MUTU TERPADU DI SMP NEGERI 3 KETAPANG - Rahadi Usman; Aswandi Aswandi; Masluyah Suib (Universitas Tanjungpura, 2020)
AbstractLeadership quality management implemented in SMP Negeri 3 Ketapang, using thestepsit does toachieveits intended purpose. These stepsare; First,the formulation ofthe conceptem bodiedin the vision, mission and goals of educationinSMP Negeri 3Ketapang. The strategy for improvingthe quality of educationinSMP Negeri 3Ketapang, includes8elements in thenational education standards, namely: first, the contentstandards. Improving the qualitytodowith thecontent standardscurriculum improvement, the use ofthe curriculumunit level. Second, thestandardprocess. Factors supporting SMP Negeri 3 Ketapang include: Source ofFund sowned, Human Resources, adequate infrastructure, presence of societies demands quality Education, Quality Improvement Program meexistence of Teachers and Education. Whileinhibiting factors experiencedin SMP Negeri 3 Ketapang is Lack of Employee Discipline, Lack of Employee commitment, moraleLack ofStudents inScience Demands, Lack of Parental Support Students Against School programKeywords: Leadership, Management, and Integrated Quality